Processos referenciais e estratégias argumentativo-retóricas como indícios do ethos discursivo do ativista LGBT - Matos, Samuel de Souza (2020)
In the context of social movements, the use of language becomes evident and relevant, constituting a social practice based on values, beliefs, ideologies and world views of specific groups. In several enunciative situations, through ethos, logos, pathos and/or other linguistic discursive strategies, activists from these movements combat hegemonic discourses and fight for social changes that guarantee them more rights and opportunities for citizen participation. Regarding the political-identity and argumentative clashes of the contemporary LGBT movement, researches in the academic field do not favor the analysis of texts produced by their activists and the construction of the discursive ethos (AMOSSY, 2008, 2018) from these subjects, especially in Aracaju/SE city. Due to this panorama, we start from the problem of defending sexual and gender diversity and the fight against LGBTphobia, in order to answer the following research question: what is the collective discursive ethos indicted by referential processes (MONDADA; DUBOIS, 2003) and strategies argumentative-rhetorical in the speech of the LGBT activist from Aracaju about their political-identity actions? In this sense, our general objective is to investigate the referential processes and argumentative-rhetorical strategies indicate the construction of the collective discursive ethos of the LGBT activist from Aracaju, thus contributing to the dialogue among Textual Linguistics (MARCUSCHI, 1983, 2008; BENTES, 2001; KOCH, 2009), the theory of Rhetorical Argumentation (PERELMAN; TYTECA, 1996; FERREIRA, 2010; FIORIN, 2018) and studies on social activism (FACCHINI, 2003; MELO, 2013; MELO, 2016; GREEN et al, 2018; MENEZES, 2018). For this endeavor, we assume the sociocognitive-interactional and rhetorical-discursive perspectives of linguistic studies and we also bet on a qualitative, descriptive and interpretive methodology (GIL, 2002; PRODANOV; FREITAS, 2013; MARCONI; LAKATOS, 2017; CAVALCANTE et al, 2016), in order to analyze the constituted corpus (open interviews), which were systematized in four thematic motives referring to the political-identity actions of LGBT activists from Aracaju: i) be LGBT in Aracaju; ii) combating LGBTphobia; iii) trans visibility and socio-legal monitoring; iv) awareness of sexual and gender diversity. The results obtained by the analyzes of this research, point, on the one hand, to the construction of an individualistic, inhuman and violent ethos of LGBTphobic people, and, on the other hand, to the indication of a resistant, courageous and thoughtful ethos of the LGBT activist from Aracaju, relating to a) the nature of their existence; b) their struggles for the human rights of the LGBT population in conjunction with municipal and state public bodies; c) their resistance(s) to LGBTphobia.